Implementing SAP from end-to-end business process scenarios. (26th April 2006) - Bubak, Oldrich; Farley, Robin Lee; Goebels, Carsten; Gonzalez, Pier; Gulledge, Thomas; Russell, Robert
Business processes extend across functional and organisational boundaries. In this 'real world', supporting information systems must be implemented using an end-to-end viewpoint to ensure a true business process orientation. Recent technology developments now enable solution implementations that are aligned with business processes. This paper presents a methodology for implementing composite solutions that span the enterprise. Given a heterogeneous IT landscape composed of both SAP and non-SAP components, a generic order execution scenario is used to derive a company-specific reference model. The model is documented in the IT architecture where business objects are mapped into a composite solution. Commercial products that are used to illustrate the methodology include SAP NetWeaver and ARIS Process Performance Manager and modelling tools. An overview of the key components that are critical to the understanding of reference model approach is given.